Using data-rich maps to improve small-scale agriculture - International Livestock Research Institute (International Livestock Research Institute, 2009)
Environmental, climatic and population changes are triggering outbreaks of diseases, some of them new and lethal, among people and their animals. Two hundred medical, veterinary and climate experts from around the world unite in search of solutions.